Exploring the Core Prescription and Underlying Mechanism of Traditional Chinese Medicine in Treating Allergic Rhinitis in Children: A Real- World Study Based on an Illustrious Senior Traditional Chinese Medicine Practitioner - Luo, Changyong; Wang, Yuhan; He, Bing; He, Yu; Yan, Yurou; Wang, Junhong; Gu, Xiaohong (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Traditional Chinese medicine (TCM) is widely used to treat allergic rhinitis (AR) in China, especially in children. However, due to the complicated composition rules and unclear underlying mechanisms, effective herbal prescriptions’ popularization and application are limited. Purpose: This study tried to detect the core prescription of herbs in treating AR in children, reveal its mechanism based on the ingredients’ network, and explore the main signaling pathways. Methods: We screened medical records of children patients with AR who were treated by TCM in DongZhiMen Hospital from Aug 2009 to Jan 2020 and adopted a descriptive analysis method on herbal characteristics. We used association rules to mine core prescriptions and used network pharmacology to establish the ingredient-target-pathway network through online databases and TCMSP, Genecards, KEGG pathway, Excel, R-Studio, and Cytoscape software. Results: The analysis of 1,092 clinical visits highlighted that the principle of formulating prescription was as follows: ‘pungent and warm herbs were used more frequently while cold-natured herbs were paid equal attention as warm-natured herbs.’ The core prescription was formed by FangFeng, BaiZhi, CangErzi, and ChanTui. These herbs covered 130 underlying targets and 141 signaling pathways of AR, which mainly had an effect on signal transduction and immunoregulation. Conclusion: The core prescription based on these real-world clinical records includes FangFeng, BaiZhi, CangErzi, and ChanTui. It principally acts on targets of signal transduction pathways and immune pathways.
Keywords: apriori algorithm